Exploratory identification of candidate SNP markers associated with recurrent clinical mastitis in Holstein cattle - Shiho Miyata; Lijie Fan; Masahiko Ito; Jun Kambe; Satoshi Takemoto; Chunmei Li; Yuki Yamamoto; Kentaro Nagaoka (PLoS ONE, 2026)
Mastitis remains one of the most prevalent and economically significant diseases in dairy cattle worldwide. Although somatic cell count (SCC) is widely used as an indicator for mastitis diagnosis, its physiological variability limits its utility for predicting individual susceptibility. In this study, we aimed to identify genomic markers associated with recurrent clinical mastitis by defining mastitis-susceptible cows as those experiencing three or more episodes within a single lactation. Whole-genome resequencing was conducted on 50 Holstein cows (25 mastitis-susceptible and 25 healthy controls), yielding 536,184 high-quality SNPs after stringent quality control. A genome-wide association analysis identified 86 SNPs surpassing the significance threshold (–log₁₀P > 5.0), and seven candidate SNPs were evaluated in an independent cohort of 100 cows. Notably, the majority of candidate SNPs were localized on the X chromosome, suggesting a potential role for X-linked variation in mastitis immune response and disease resistance. While the candidate marker panel combining SNP1, SNP2, and SNP7 demonstrated moderate sensitivity (47%), its high specificity (98%) highlights its potential utility as a preliminary screening tool for identifying individuals at increased risk of recurrent mastitis. These findings provide a foundation for further functional validation and large-scale replication studies, which are essential for implementing effective genomic selection strategies to mitigate mastitis incidence in dairy herds.